Influence of the quality of compounds on the adhesion properties of metal cord. - O. N. Khrol (Литьë и металлургия, 2020)
The adhesive strength of the metal cord, i. e. the strength of its adhesion to the compound, is one of the most important indicators of the quality of the metal cord. Increasing the amount of adhesive strength allow to improve the performance of finished tires.Determination of the adhesive strength value can be performed by different methods. All methods are based on extracting (pulling) metal cord from a block of vulcanized rubber and fixing the required load. Each method has its own characteristics that affect the amount of adhesive strength. Therefore, when conducting comparative tests, it is necessary to use one of the selected methods.The study of factors that affect the amount of adhesive strength is necessary to identify the causes that lead to its change.The article analyzes how the quality of the used compound affects the adhesive strength. Tests with the use of compounds with various defects were considered and carried out; probable factors leading to deviations in the adhesion strength indicators were determined.